(untitled) (Journal of Kidney Cancer, 2022)
While the gold-standard for management of localized renal cell carcinoma (RCC) is partial nephrectomy, recent ablative strategies are emerging as alternatives with comparable rates of complications and oncologic outcomes. Thermal ablation, in the form of radiofrequency ablation and cryoablation, is being increasingly accepted by professional societies, and is particularly recommended in patients with a significant comorbidity burden, renal impairment, old age, or in those unwilling to undergo surgery. Maturation of long-term oncologic outcomes has further allowed increased confidence in these management strategies. New and exciting ablation technologies such as microwave ablation, stereotactic body radiotherapy, and irreversible electroporation are emerging. In this article, we review the existing management options for localized RCC, with specific focus on the oncologic outcomes associated with the various ablation modalities.